Azospirillum brasilense e reguladores vegetais na mitigação dos efeitos da intoxicação por mesotriona no milho e do déficit hídrico na soja - Bulegon, Lucas Guilherme (2019)
The use of herbicides in the control of weeds is fundamental in agricultural productivity, however, some even selective herbicides result in crop intoxication. Another condition of very important condition is the water limitation that reduces the productivity of crops. Thus, this thesis was to evaluate the inoculation of plant growth promoting bacteria Azospirillum brasilense in seeds or foliar spray as well plant growth regulator in foliar spray, in reduction of oxidative stress caused by herbicide inhibitors of carotenoid synthesis in maize and drought in soybean. For this, three experiments were developed in corn, one in greenhouse for evaluation of the biometric, physiological and biochemical variables and two under field conditions for evaluation of the production components. In both the local experiments were carried out in randomized blocks in a 4x2, and four replications. The first factor was composed of treatments: control; seed inoculation with A. brasilense; foliar spray application with A. brasilense; and foliar spray application of plant growth regulation with auxin, gibberellin and cytokinin. Foliar spray treatments were applications in tank mix with herbicide mesotrione (192 g ha-1) in V3 stage. The second factor was formed for presence or absence of mesotrione. The results obtained demonstrate that the application of mesotrione reduces the gas exchanges of maize and the treatments applied not protect the maize from the intoxication provided by the herbicide, and do not increase the productivity of the crop. A randomized block design was used for soybean with five treatments and five replications: irrigated control; drought control; seed inoculation with A. brasilense in drought; foliar spray application A. brasilense in drought; foliar spray application auxin, gibberellin and cytokinin in drought. The imposition of drought occurred in full bloom, with daily evaluations. The evaluation consisted of soil gravimetric moisture, relative water content, photosynthetic response curves in function of different photon flux densities, gas exchange, chlorophyll a fluorescence, antioxidant enzyme activity, photosynthetic pigment content, and production components per plant at the end of the crop. In general, the results show that the foliar spray application of A. brasilense or plant growth regulator alleviates the effects of the drought in photosynthetic curves, in gas exchange, in chlorophyll a fluorescence, in photosynthetic pigment content and increase the activity of the enzyme system by reducing lipid peroxidation. When considering the production by plants all the treatments employed mitigate the losses in relation to the drought control. Therefore, the use of A. brasilense via seed or foliar spray application and plant regulators via foliar spray do not bring beneficial effects on the intoxication of corn with mesotrione. However, when considering the drought in the soybean, the treatments soften the losses in yield per plant due to mitigate the effects on plant biochemical and physiological system.